Navigating issues of inequity in ELT: An interview with Associate Professor Nathanael Rudolph - M. Faruq Ubaidillah; Mutmainnah Mustofa (English Language Teaching and Research Journal (ELTAR-J), 2020)
Nathanael Rudolph is an associate professor of sociolinguistics and language education at Kindai University in Higashiosaka, Japan. His research interests include translingual practice, critical approaches to language teacher and learner identity, and (in)equity in (and beyond) language education.